Assessment of sexuality in patients with Peyronie's disease - Moussaab Rachid; Gallouo M; Graiouid M; Allali S; Seffar A; Dakir M; Debbagh A; Aboutaieb R (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2020)
Introduction: Peyronie's disease is an acquired fibrosis of the corpora cavernosa which causes deformation of the penis and represents one of the causes of erectile insufficiency with serious consequences for the life of a couple. The diagnosis is clinical and the treatment is medico-surgical. Objective: Evaluation of the sexuality of patients with Peyronie's disease.  Patients and methods: This prospective study occured from February 2017 to December 2019 including patients suffering all from Peyronie's Disease (PD). The IIEF (International Index of Erectile Function), EHS (Erection Hardness Score) and T LUE scores were used to assess erectile function and the severity of PD. The pre-established data were: Age, co-morbidities, delays, medical background, the onset mode, data from the penis examination in the flaccid state and in erection, general examination and therapeutic management. Results: We listed 20 patients; the average age is 58.2years (39-69years). The onset was progressive in 80% of the patients; the average consultation time was 14.1 months. Deformation was the most frequent symptom in 70% of cases, followed by the coital discomfort in 50%. Intromission was accompanied by a discomfort in 60%. In 80% of patients the disease was at the sclerotic stage. Palpation of the plaque was found in 60% of patients. The IIEF score was 14,6 and 80% of patients had erectile dysfunction, 40% of which was moderate. Grade 4 EHS was predominant in 60%, pain was mild in erection in 40% case. Dyspareunia has been reported by 60% of partners. Medical treatment was prescribed for 60% of our patients, 40% of whom received medical treatment for the dysfunction. Conclusions: PD significantly alters the sexual and relational quality of patient's lives.